2014
DOI: 10.1063/1.4903834
|View full text |Cite
|
Sign up to set email alerts
|

A two degrees-of-freedom piezoelectric single-crystal micromotor

Abstract: A two degrees-of-freedom (DOF) ultrasonic micromotor made of piezoelectric Pb(In 1/2 Nb 1/2 ) O 3 -Pb(Mg 1/3 Nb 2/3 )O 3 -PbTiO 3 (PIN-PMN-PT) single crystal square-bar (dimensions 2 Â 2 Â 9 mm 3 ) was developed. The PIN-PMN-PT square-bar stator can generate standing wave elliptical motions in two orthogonal vertical planes by combining the first longitudinal and second bending vibration modes, enabling it to drive a slider in two orthogonal directions. The relatively large driving forces of 0.25 N and motion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Academic research groups are also reporting interesting findings using L1B2 mode. A single crystal-based stator with 2 mm × 2 mm × 9 mm has demonstrated 2-degrees-of-freedom linear motions with a force of 250 mN and a velocity of 35 mm/s [117]. The smallest one of using L1B2 mode might be 5 mm × 1.5 mm × 1.45 mm, but the performance parameters have not been indicated [118].…”
Section: Review Of Linear Ultrasonic Micromotorsmentioning
confidence: 99%
“…Academic research groups are also reporting interesting findings using L1B2 mode. A single crystal-based stator with 2 mm × 2 mm × 9 mm has demonstrated 2-degrees-of-freedom linear motions with a force of 250 mN and a velocity of 35 mm/s [117]. The smallest one of using L1B2 mode might be 5 mm × 1.5 mm × 1.45 mm, but the performance parameters have not been indicated [118].…”
Section: Review Of Linear Ultrasonic Micromotorsmentioning
confidence: 99%
“…It can be seen that the step motion velocity decreases almost linearly with the load, and it is found that the max load force of the DMMLA in step mode is 5.5 N. The relationship of displacement and time under different loading condition is presented in Figure S5. Compared with ultrasonic motors, the step mode of the DMMLA apparently shows a better loading performance due to its quasistatic motion [36,37].…”
Section: Piezoelectricmentioning
confidence: 99%
“…The second kind of structure is the compact structure in parallel [6][7][8][9], for which the motions often share a common friction interface [6,8] that leads to a coupled motion when the motions are operated at the same time [8,10]. Recent studies on parallel PIDMs have attained multi-DOF motions by using different modes of vibration under ultrasonic driving [8,[11][12][13][14][15], and studies on series PIDMs have achieved multi-DOF motions by avoiding coupled motions [4,5,16]. However, there are few studies on the coupled motion characteristics of the parallel impact PIDM [17,18].…”
Section: Introductionmentioning
confidence: 99%